2D QSAR Approach to Develop Newer Analogs as Melatonin Receptor Agonist (Dhaka University Journal of Pharmaceutical Sciences, 2016)
QSAR analysis was performed using 20 MT1 agonist and 18 MT2 agonist. MODI was 0.6373 in case of MT1 agonist and 0.6299 in case of MT2 agonist. QSAR model for MT1 receptor agonist was pKd = 16.24793(+/- 0.93539) +1.0924(+/-0.18831) ALogP -0.11399(+/-0.01383) apol +0.59876(+/-0.16599) C2SP3 -10.29435(+/-2.81413) E3p and for MT2 receptor agonist was pKd = 6.38692(+/-0.91098) +0.87139(+/-0.20258) ALogP -0.0351(+/-0.00542) AMR +3.33079 (+/-0.80377) SpMin6_Bhm +146.76208(+/-28.14492) VE2_Dt with statistical parameter as Q^2:0.79167, r^2 :0.88878, |r0^2-r'0^2|:0.04633,k:1.03159, [(r^2-r0^2)/r^2]:0.01013, k':0.96695, [(r^2- '0^2)/r^2]:0.06226 and Q^2:0.81401, r^2:0.97384, |r0^2-r'0^2|:0.1039, k:0.98543, [(r^2-r0^2)/r^2]:0.08048, k':1.01351, [(r^2-r'0^2)/r^2]:0.18717 respectively; comply with the Golbraikh and Tropsha acceptable model criteria. The results from MLR Y Randomization test in case of MT1 agonist was cRp^2: 0.7665 and MT2 agonist was cRp^2: 0.7284. Applicability domain were identified by Euclidean and Mahalanobis Distance Method. Finally it was clear that all the predicted data are inside the area of observed data points and also some data are purely overlapped.Dhaka Univ. J. Pharm. Sci. 15(1): 7-19, 2016 (June)